2022
DOI: 10.1038/s41598-022-11329-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based optimization of pre-symptomatic COVID-19 detection through smartwatch

Abstract: Patients with weak or no symptoms accelerate the spread of COVID-19 through various mutations and require more aggressive and active means of validating the COVID-19 infection. More than 30% of patients are reported as asymptomatic infection after the delta mutation spread in Korea. It means that there is a need for a means to more actively and accurately validate the infection of the epidemic via pre-symptomatic detection, besides confirming the infection via the symptoms. Mishara et al. (Nat Biomed Eng 4, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For instance, Mishara et al reported a comprehensive study where physiological data from smartwatches were used to predict COVID-19 presymptomatic cases [ 90 ]. Inspired by this work, many machine learning algorithms have been reported in recent studies [ 91 , 92 ] and are equally important for MPXV detection. It is important to know the virus’s infectiousness status after infection.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…For instance, Mishara et al reported a comprehensive study where physiological data from smartwatches were used to predict COVID-19 presymptomatic cases [ 90 ]. Inspired by this work, many machine learning algorithms have been reported in recent studies [ 91 , 92 ] and are equally important for MPXV detection. It is important to know the virus’s infectiousness status after infection.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…LSTM has also been used for detecting congestive heart failure [ 116 ]. Cho et al claimed that one-class SVM provided a 23.5–40% earlier detection of COVID-19 compared to the LSTM method [ 79 ]. LSTM has also been applied for estimating sleep stages from wearable data [ 117 ].…”
Section: Role Of Machine Learning In Diagnosticsmentioning
confidence: 99%
“…Cho et al. improved upon that study by proposing a One Class-Support Vector Machine (OC-SVM) for pre-symptomatic COVID-19 detection ( Cho et al, 2022 ). Their method improved the presymptomatic detection performance over the statistical method proposed by Mishra et al.…”
Section: Introductionmentioning
confidence: 99%